Application of high‐dose‐rate endorectal brachytherapy in the treatment of locally advanced rectal cancer - Tianyao Wang; Yifan Tao; Guanghui Gan; Long Chen; Yuan Xu; Fei Sun; Xiaoting Xu (Precision Radiation Oncology)
Abstract Purpose This study evaluates the efficacy, toxicity, and survival impact of high‐dose‐rate endorectal brachytherapy (HDR‐EBT) as neoadjuvant therapy for locally advanced rectal cancer. Methods A review of 16 studies from PubMed, Embase, and Web of Science (1990–2023) was conducted. Results Patients treated with HDR‐EBT alone had a pathological complete response (pCR) rate of 23.7%–35.3% (mean: 24.3%), anal preservation rate of 12.2%–74.9% (mean: 41.8%), and 5‐year progression‐free survival rate of 64.6%–65.4% (mean: 65.3%). When combined with concurrent long‐term radiotherapy and chemotherapy, pCR rates improved from 18.1%–55.0% (mean: 31.0%), with anal preservation rates of 39.6%–51.4% (mean: 45.3%). However, overall survival did not significantly improve. Conclusion Integrating advanced techniques such as intensity‐modulated radiation therapy (IMRT) with HDR‐EBT shows promise. This approach particularly benefits patients ineligible for surgery or those adopting a watch‐and‐wait strategy after complete clinical remission, thus highlighting the potential of HDR‐EBT in this treatment landscape.